Comprehensive Analysis of Ferroptosis Regulators With Regard to PD-L1 and Immune Infiltration in Clear Cell Renal Cell Carcinoma - Wang, Song; Chen, Shiming; Ying, Yufan; Ma, Xueyou; Shen, Haixiang; Li, Jiangfeng; Wang, Xiao; Lin, Yiwei; Liu, Ben; Zheng, Xiangyi; Xie, Liping (Frontiers in Cell and Developmental Biology, 2021)
Clear cell renal cell carcinoma (ccRCC) is one of the tumor types with sensitivity to ferroptosis, and immunotherapy has emerged as a standard pillar for metastatic ccRCC treatment, while it remains largely obscure whether ferroptosis influence the tumor immune microenvironment (TIME) in ccRCC. Based on the available data in The Cancer Genome Atlas (TCGA), divergent expression profiles of ferroptosis regulators were noted in ccRCC and normal tissues, and we also found that the ferroptosis regulators correlated with the PD-L1 expression. Two independent subtypes were determined by consensus clustering analysis according to the expression level of ferroptosis regulators in ccRCC. The cluster 1 showed lower histological tumor stage and grade, more favorable prognosis and higher PD-L1 expression compared to cluster 2. CIBERSORT analysis revealed that cluster 2 harbored higher infiltrated levels of CD8+ T cell, Tregs and T follicular helper cell, while cluster 1 more correlated with the Monocyte, M1 Macrophage and M2 Macrophage. Gene set enrichment analysis (GSEA) indicated that ERBB signaling and JAK_STAT signaling pathway were significantly enriched in the cluster 1. We subsequently identified CARS as the potentially key immune infiltration-related ferroptosis regulator, whose high expression showed dismal prognosis and was positively correlated with PD-L1 expression in ccRCC, we also verified the upregulation of CARS in ccRCC tissues and cell lines via qRT-PCR method Additionally, a pan-cancer analysis demonstrated that CARS closely related to the expression of immune checkpoint-related genes (especially PD-L1) and unfavorable prognosis in diverse cancer types. In summary, our study suggested that the crucial role of ferroptosis in immune infiltration of ccRCC, and CARS is a potentially novel prognostic biomarker and potential target for cancer immunotherapy.